Mengenal Sepintas Islam Nusantara - Ngatawi Al-Zastrouw (Laboratorium Prodi Pendidikan Agama Islam UNJ, 2017)
The present research explains the basic concept of Islam Nusantara (IN) and its related concepts. IN is a concept that explains the patterns of thought and behavior of Indonesian moslims as reflections of the way they comprehend, teach and implement the Islamic teaching which have a typical of Nusantara. IN is not a new school in the history of Islam. It is about methods (manhaj) and manners (kayfiyah) used by Muslim scholars in Nusantara to spread the Islamic teachings, which can be easly understood and implemented by the people of Nusantara. In addition it also a means of preserving authenticity and validity of Islamic teaching by protecting the fundamental tanets of Islam (usul) and at the same time opening the opportunity for creativity to the non fundamental tanets of Islam (furu‘). By doing so, it will create a pattern of thought, tradition, culture and character if Islam, which are tipical of Nusantara.